Choices and effects of different green labels in the EU bond market - Peng Zhou; Shijie Jin; Khelifa Mazouz; Wenjie Ding (Cardiff University, Cardiff Business School, 2024)
This paper demonstrates that green-labeling forms an integral part of financial investment vehicles. We use data from the EU green bond market to show that green labels reduce the required yields on bonds (the "greenium") in the long run, with the effect being more pronounced when labels are externally certified. We also find that green bonds can increase investors' short-term attention when they are externally labeled. Further evidence suggests that the greenium of self-labeled green bonds is mainly attributed to a weak signaling effect, whereas that of externally-labeled bonds results from a combination of signaling effect and pro-environmental preferences. Our findings indicate that investors value the reassurance that third-party certifications provide about the ethical use of bond proceeds. This highlights the potential benefits of introducing stricter oversight of green bond proceeds in the bond market.
Keywords: G12; G41; Q59; 330; Green Bond Label; Signaling Effect; Pro-environmental Taste